PTH-098 68ga-dotatate Pet In Localising Neuroendocrine Tumours – Could This Be The State Of The Art Diagnostic Test?. (9th June 2014) - Wu, J; Ramage, J; Prachalias, A; Srirajaskanthan, R; Sherwood, R; Mulholland, N
Abstract : Introduction: 68Ga-DOTATATE PET is an established tool for localising primary tumour in metastatic neuroendocrine tumours (NETs) and in identifying NET metastases not seen on cross-sectional imaging. There is increasing evidence regarding its role in detecting occult primary sites in suspected NET. We present our experience of patients with primary gastrinoma/insulinoma seen only on Ga-DOTATATE imaging. Methods: Patients reviewed in King's College Hospital between 2005–2011 were included. Ga-DOTATATE was performed if there was a high degree of clinical suspicion of NET with supportive biochemistry but negative imaging and endoscopy. Results: Patients with primary gastrinoma/insulinoma identified only with Ga-DOTATATE are presented below. A 61 year-old male with dyspepsia and diarrhoea experienced multiple spontaneous jejunal perforations. Fasting gastrin and chromogranin A were elevated (>700 and 106 pmol/L respectively). Octreoscan showed a possible abnormal area in the pancreatic body not seen on CT, MRI, PET-FDG or EUS. DOTATATE revealed a soft tissue density in the pancreatic head. Post-Whipples histology confirmed NET tumour in peri-pancreatic lymph nodes. A 64 year-old female presenting with an upper gastrointestinal bleed from extensive duodenal ulceration was found to have an elevated fasting gastrin level (>400 pmol/L) but a normal CT and Octreoscan. DOTATATE identified a focus within the gastrinoma triangle. Resection confirmed a 15 mm nodule of peri-pancreatic tumour with histological evidence of endocrine differentiation of low grade and proliferative rate. A 77 year-old non-diabetic male with irritable bowel symptoms presented with spontaneous duodenal perforation and developed episodes of hypoglycaemia (glucose 0.2 mmol/l) with an inappropriately elevated insulin (14.3 mU/l) and c-peptide (1063 pmol/l). Gastrin was raised (55 pmol/l). CT, MRCP, MRI pancreas and EUS were unremarkable. DOTATATE showed a small lesion in the pancreatic tail. Surgical enucleation of the lesion revealed a well differentiated NET histologically. Conclusion: These cases support the use of Ga-DOTATATE as a potential diagnostic tool in suspected but not yet localised primary cases of gastrinoma/insulinoma with symptoms or elevated blood levels of tumour markers where cross-sectional imaging is normal or equivocal. To date calcium stimulation with selective angiography has been used. Ga-DOTATATE may obviate the need for this invasive and highly complex test. Larger case series and prospective data are needed to look at the validity of this test and ascertain its role in routine clinical practice. Disclosure of Interest: None Declared.